Wat w Polsce powojennej. Tezy - Pietrych, Piotr (Colloquia Litteraria, 2012)
Wat in postwar Poland. Theses A postwar period (1946–1953) in Wat’s literary output is usually omitted by the critics (exceptions are Venclova and Ritz). Difficulties in making comments on this period perhaps stem from that which does not usually fit what critics write about Wat (for instance, that fact that since his arrival from Kazakhstan he was a confirmed anticommunist) and what he published then. A puzzling is the presence in Wat’s works (e.g. in Antyzoil) unanimous declarations of the support for the postwar political order. However, when Wat followed some voice of disagreement, it sounded silent, unconvincing (criticism of the project of realism in literature). A positive involvement in Polish reality at that time was certainly connected with Wat’s personal experiences who, having arrived from his wandering from the Soviet Union to Poland, felt it as “paradise” (this is the name he referred to Poland in Mój wiek [My Century]), seemed not to perceive that it was only a “sham” of paradise. Besides, Wat wanted to participate in Polish cultural life, especially because in postwar years he started to feel literary unfulfilment and a strong need to return to writing. A particularly meaningful example in this context is Wat’s unsuccessful drama of Kobiety z Monte Olivetto [Women from Monte Olivetto] – the writing of which was for the poet the act of desperation and it created a paradox: wanting to participate in postwar literary life in Poland, Wat decided to “collaborate with Social Realism” (Zdzisław Łapiński’s definition), in order to achieve his goal.